MEMORI KOLEKTIF SUKU TOHU DAN SUKU TANGANANG: ANALISIS MEMORI KOLEKTIF SUKU TOHU DAN SUKU TANGANANG BERDASARKAN TEORI HALBWACHS - Yulite Mariska Dima (Institut Agama Kristen Negeri Kupang, 2026)
ABSTRACTThe Conflict between the Tohu and Tanganang tribes originated from the murder of Katonga Retang, a missionary commissioned by the Ductch Colonial government to spread the Gospel to the indigenous tribes of Sumba /Marapu, including the Tanganang. This event sparked a hostility that lasted nearly a century, perpetuated through customary prohibitions governing the relationship between the two tribes.This study analizes how the collective memory of this event was formed, preserved, and reproduced by both tribes, eventually serving as the foundation for reconciliation in 2024. utilizing Maurice Halbwach’s theory, the reseaech demonstrates that the collective memory of both tribes is selective, structure, and dependent on the social frameworks that shape their social identities.The findings indicate that colletive memory is not always synonymous with objective history: the inherited narratives emphasize emotional, symbolic, and group-identity aspects over factual accuracy. The reconciliation process was made possible through a reconstruction of memory initiated by the executive board of the synod of the Cristian Church of Sumba (BPMS GKS). this opened a space for the reinterpretation of a shared history and a shift in social identity from hostility toward peace. This study affirms that collective memory can serve as both a source of conflict and a means of healing, depending on how social groups reorganize their narrative within the framework of identity and social relations.